2020
DOI: 10.1038/s41598-020-58544-z
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of next generation sequencing analysis pipelines for HIV-1 drug resistance testing

Abstract: Next generation sequencing (NGS) is a trending new standard for genotypic HIV-1 drug resistance (HIVDR) testing. Many NGS HIVDR data analysis pipelines have been independently developed, each with variable outputs and data management protocols. Standardization of such analytical methods and comparison of available pipelines are lacking, yet may impact subsequent HIVDR interpretation and other downstream applications. Here we compared the performance of five NGS HIVDR pipelines using proficiency panel samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 53 publications
2
58
0
Order By: Relevance
“…Chest computed tomography (CT) scan is a kind of radiography and medical imaging using X-ray to figure out any alteration of lung tissue, which sometimes could be helpful to unspecific diagnosis of respiratory viral infections such as coronavirus infection. Regarding the clinical manifestation of COVID-19, CT scan can be used to confirm coronavirus infection as a cause of lung involvement by showing bilateral multilobar ground-glass opacification (GGO) with a peripheral or posterior distribution [ 30 ]. A study in Wuhan, China, on COVID-19 patients, showed that CT scans had a sensitivity of about 98%, which is of particular importance compared to a 71% sensitivity of RT-PCR [ 30 ].…”
Section: Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest computed tomography (CT) scan is a kind of radiography and medical imaging using X-ray to figure out any alteration of lung tissue, which sometimes could be helpful to unspecific diagnosis of respiratory viral infections such as coronavirus infection. Regarding the clinical manifestation of COVID-19, CT scan can be used to confirm coronavirus infection as a cause of lung involvement by showing bilateral multilobar ground-glass opacification (GGO) with a peripheral or posterior distribution [ 30 ]. A study in Wuhan, China, on COVID-19 patients, showed that CT scans had a sensitivity of about 98%, which is of particular importance compared to a 71% sensitivity of RT-PCR [ 30 ].…”
Section: Detection Methodsmentioning
confidence: 99%
“…Regarding the clinical manifestation of COVID-19, CT scan can be used to confirm coronavirus infection as a cause of lung involvement by showing bilateral multilobar ground-glass opacification (GGO) with a peripheral or posterior distribution [ 30 ]. A study in Wuhan, China, on COVID-19 patients, showed that CT scans had a sensitivity of about 98%, which is of particular importance compared to a 71% sensitivity of RT-PCR [ 30 ]. The findings of CT scan are usually unspecific and are the same as other types of pneumonia; however, the combination of this imaging with other diagnostic techniques such as real-time PCR or biosensing as the confirmation could be useful to recognize COVID-19 patients.…”
Section: Detection Methodsmentioning
confidence: 99%
“…The other variant callers include ShoRAH (Zagordi et al, 2011) and its extension (McElroy et al, 2013), SNVer (Wei et al, 2011), deepSNV (Gerstung et al, 2012), SAMtools (Li, 2011), GATK (McKenna et al, 2010, Ion-Torrent specific TVC and others. For comparison and evaluation of different methods, please refer to the dedicated reviews or comparative work (Hwang et al, 2015;Lee et al, 2020;Pereira et al, 2020). In short, each method has its own pros and cons.…”
Section: Specific Considerations In Bioinformatics Data Analyses To Dmentioning
confidence: 99%
“…Several bioinformatics tools or pipelines for variant calling have been developed specifically for studying viral variants (Huber et al, 2017;McElroy et al, 2013;Verbist et al, 2015;Zagordi et al, 2010) and calculating the complexity of a quasispecies as well as measuring the genetic distance between two similar quasispecies (Marinier et al, 2019). Many more variants callers have been discussed and compared in dedicated reviews or methodological comparison papers (Hwang et al, 2015;Lee et al, 2020;Pereira et al, 2020). Implementing an existing variant-calling tool in NGS data analysis is relatively simple and saves additional costs for sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Often these tools either target specific viruses (Huber et al, 2017;Wymant et al, 2018;Howison et al, 2018;Taylor et al, 2019) or correspond to proof-of-concept implementations with limited support for broader applications. For HIV drug resistance testing, Lee et al (2020) have recently evaluated various bioinformatics pipelines for this specific application.…”
Section: Introductionmentioning
confidence: 99%